The political economy of violence against women - True, Jacqui (Oxford studies in gender and international relations, 2012)
Violence against women is a major problem in all countries, affecting women in every socio-economic group and at every life stage. Yet, when women enjoy good social and economic status they are less vulnerable to violence across all societies. This book develops a political economy approach to understanding violence against women - from the household to the transnational level - accounting for its globally increasing scale and brutality.